Protagonis Yang Tak Disebutkan Namanya: Infertilitas Perempuan Dan Patriarki Dalam Hakim-Hakim 13:1-25 - Danella Koni Madeline Rewah (Sekolah Tinggi Teologi Sriwijaya, 2022)
Abstract: The sensational story of Samson's birth grabs the reader's attention which made the role of the nameless mother not stand out. This situation becomes urgent for the author to reveal the hidden polemics and elevate the existence of women in the patriarchal cultural ideology implied in this text. This theological thinking is structured through a socio-rhetorical approach to identify the rhetorical techniques that exist in Judges 13:1-25 and analyze from a feminist perspective. The results of this analysis represent the writer of Judges uses irony and paradox in compiling this story to show a polemical feature and create the narration of Judges 13:1-25 as a counter-cultural rhetoric illustration used to replace the dominant ideology with an alternative ideology. This text contributes to the horizon of the reader’s theological thinking to acknowledge and appreciate the existence of marginalized society, especially women infertility who frequently experience discrimination. Abstrak: Kisah sensasional kelahiran Simson menyita fokus pembaca sehingga tidak menonjolkan peran ibunya yang namanya tidak diketahui. Situasi ini menjadi urgensi bagi penulis untuk mengungkap polemik tersembunyi dan mengangkat eksistensi perempuan dalam ideologi budaya patriarki yang tersirat dalam teks ini. Pemikiran teologis ini disusun melalui pendekatan sosio-retoris untuk mengidentifikasi teknik retorika yang terdapat dalam Hakim-Hakim 13:1-25 dan menganalisisnya dengan perspektif feminis. Hasil analisis menunjukkan bahwa penggunaan ironi dan paradoks penulis dalam menyusun kisah ini memperlihatkan sifat polemik dan menjadikan narasi Hakim-Hakim 13:1-25 sebagai ilustrasi retorika kontra budaya yang digunakan untuk menggantikan ideologi dominan dengan ideologi alternatif. Tulisan ini memberikan kontribusi bagi pemikiran teologis pembaca agar mengakui dan menghargai keberadaan kaum marjinal, khususnya perempuan mandul yang sering mengalami diskriminasi.